Total Phenolic Content, Antioxidant and Antibacterial Activities of Sargassum polycystum of Ethanol Extract from Waters of Kabung Island - Safitri, Ikha; Warsidah, W.; Sofiana, Mega Sari Juane; Kushadiwijayanto, Arie A.; Sumarni, T. Novi (BERKALA SAINSTEK, 2021)
Sargassum policystum is one of the genus Sargassum from the brown macroalgae group which has an abundance of chemical constituents of fucoidan, fucoxanthin, phenolic acids and alginate which have important biological activities, such as antioxidants and antibacterials. This species thrives in the waters of Kabung Island, Bengkayang, West Kalimantan and has not been exploited so that it tends to act as a marine weed. This study aimed to determine the total phenolic content of the ethanolic extract of S. policystum and its antioxidant and antibacterial activity. Determination of the total content of phenolic compounds using the Folin Ciocalteu method, antioxidant testing using the DPPH method (2,2-diphenyl-1-picrylhydrazyl) and the indicator of sample color change with the addition of these radicals was measured by UV-Vis spectrophotometer. Antibacterial testing was carried out by the test sample diffusion method and the inhibition of the growth of the test bacteria Staphylococcus aureus and Escherichia coli as test bacteria was indicated by the formation of a clear area around the sample wells. The results showed that the phenol content of the ethanolic extract of S. policystum was 79.8 mg/g extract, its antioxidant activity (IC50) was 98.903 ppm, classified as a strong antioxidant, while the comparison antioxidant, Vitamin C, had an IC50 of 6.26 ppm. The inhibitory ability of the ethanol extract against the test bacteria used was indicated by the formation of the largest inhibition diameter on S. aureus of 12.4 mm and E. coli of 12.0 mm.